1995
DOI: 10.1111/j.1365-2958.1995.tb02216.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the chaperonin families (HSP60, HSP 10 and TCP‐1) of proteins and the origin of eukaryotic cells

Abstract: SummaryThe members of the 10 kDa and 60 kDa heat-shock chaperonin proteins (HspiO and Hsp60 or Cpn10 and Cpn60), which form an operon in bacteria, are present in all eubacteria and eukaryotic ceil organelles such as mitochondria and chloropiasts. In archaebacteria and eukaryotic cetl cytosoi, no close homologues of Hsp10 or Hsp60 have been identified. Ho\wever, these species (or ceil compartments) contain the Tcp-1 family of proteins (distant homologues of Hsp60). Phylogenetic analysis based on global alignmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
176
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(192 citation statements)
references
References 70 publications
13
176
0
3
Order By: Relevance
“…Previously published gltA sequence similarities among the Bartonella taxa ranged from 83-8 to 91 % (Birtles & Raoult, 1996), indicating that the DNA sequence diversity of groEL falls unevenly between 16s rRNA and gltA. Comparing the results of these phylogenetic reports on Bartonella species (namely 16s rRNA and gZtA) with this report is hampered because these two genes and groEL are not equivocal, since each group of sequences (Birtles & Raoult, 1996) (Benachenhou-Lahfa et al, 1994;Birtles & Raoult, 1996;Brown et al, 1994;Creti et al, 1991 ;Gupta, 1995 ;Karlin et al, 1995 ;Kruse et al, 1996 ;Kumada et al, 1993;Roux et al, 1997;Tiboni et al, 1993;Viale et al, 1994;Wang & Shakes, 1996). These studies and others have clearly shown that phylogenies based on different genes show discrepancies.…”
Section: Comparison Of 165 Rrna and Groel Phylogeniesmentioning
confidence: 39%
“…Previously published gltA sequence similarities among the Bartonella taxa ranged from 83-8 to 91 % (Birtles & Raoult, 1996), indicating that the DNA sequence diversity of groEL falls unevenly between 16s rRNA and gltA. Comparing the results of these phylogenetic reports on Bartonella species (namely 16s rRNA and gZtA) with this report is hampered because these two genes and groEL are not equivocal, since each group of sequences (Birtles & Raoult, 1996) (Benachenhou-Lahfa et al, 1994;Birtles & Raoult, 1996;Brown et al, 1994;Creti et al, 1991 ;Gupta, 1995 ;Karlin et al, 1995 ;Kruse et al, 1996 ;Kumada et al, 1993;Roux et al, 1997;Tiboni et al, 1993;Viale et al, 1994;Wang & Shakes, 1996). These studies and others have clearly shown that phylogenies based on different genes show discrepancies.…”
Section: Comparison Of 165 Rrna and Groel Phylogeniesmentioning
confidence: 39%
“…Org., organism; perm., permease; RNAP, RNA polymerase; k-ase, kinase; RNaseP, RNaseP RNA. The sequence sources were the genome Web sites (see Web Site References in Supplemental Material, Table S3, online) and Conway de Macario et al 1994, Gupta and Singh 1993, Macario et al 1991, 1993, 1995, Hoffman-Bang et al 1999, Deppenmeir et al 2002, Galagan et al 2002, Smith et al 1997 , and A.S. Kazi and C.K.K. Nair, Bombay, India (accession number AF069527; gi, 10798841; H. mediterranei).…”
Section: Dnak Locus I Types and Dnak Phylogenymentioning
confidence: 99%
“…If the changes exceed a certain degree of intensity and/or duration, the cell stress may reach a dangerous level and may cause cell damage or even death (Georgopoulos et al 1990;Linquist 1992;Nollen and Morimoto 2002). Cells have mechanisms to deal with stress and its consequences (e.g., protein denaturation); these mechanisms include the chaperoning systems (Missiakas et al 1996;Linquist 1992;Bukau et al 2000;Macario and Conway de Macario 2001;Young et al 2004), which exist in all organisms and in all cells, tissues, and organs of multicellular life forms (Gupta 1995;Gupta and Golding 1996;Bustard and Gupta 1997;Gupta et al 1997;Karlin and Brocchieri 1998;Willison 1999;Brocchieri and Karlin 2000;Karlin and Brocchieri 2000;Laksanalamai et al 2004;Kultz 2005). The universality of the chaperoning systems testifies to their importance and, also, shows that assisted protein folding, as well as refolding of denatured or misfolded polypeptides, is essential for life.…”
Section: Introductionmentioning
confidence: 99%
“…Several duplication and HGT fl ux the phylogeny of PFK [121]. Conservation Aquifex aeolicus and Thermotoga maritima Large number of genes that are most similar in their protein [117] Archaeoglobus fulgidus Fatty acid metabolism; Tryptophan biosynthesis pathway closely related to eubacterium Bacillus subtilis [73,117] Bacillus subtilis and B. halodurans Prophage like regions [117] Bacteria and fungi ß-glucuronidase (gus) genes [159] Bacteria and archaea FtsZ, a cell division protein [160,161] Bacteria and rumen Ciliates Expressed genes [162] Chlamydia trachomatis Polymorphic membrane protein C gene [163] Clostridium acetobutylicum 3-Isopropylmalate dehydratase, small subunit 3-Isopropylmalate dehydratase, large subunit 2-Isopropylmalate synthase [164] Cyanobacteria and α-proteobacteria (Rickettsia and Ehrlichia) are nearest to chloroplast and mitochondria HSP60, a major bacterial antigenic protein [165,166] Cyanobacteria and γ-proteobacteria ArsC gene (arsenate reductase) [167] Cyanobacteria and chloroplast genome of Euglena myxocylindracea psbA intron [168] Deinococcus radiodurans dTDP-4-dehydrorhamnose epimerase (Lipopolysaccharide biosynthesis) [118,164] …”
Section: Transcription and Regulatory Activitiesmentioning
confidence: 99%